PENERAPAN METODE K-MEANS UNTUK PROSES PENENTUAN BANTUAN LANGSUNG TUNAI (BLT) PADA DESA MEKAR SARI KECAMATAN KUMPEH KABUPATEN MUARO JAMBI - Puad, Lailyn; Limia Budiarti, Rike; -, Rismawati (JURNAL AKADEMIKA, 2024)
Direct Cash Assistance is a government assistance program that provides cash for the poor. Poverty is also a factor in people's inability to meet their daily needs, causing difficulties in meeting their basic needs. For data collection, secondary data came from various literature related to direct cash assistance. Based on the data that has been explained, the findings in the implementation of direct cash assistance are not yet optimal because various kinds of problems are still found, such as discrepancies in providing direct cash assistance, which aims to assist in the calculation process according to those who are less fortunate or who deserve assistance. cash straight away. To classify recipients of this assistance, the K-Means method is used to analyze an object that is included in the class attribute in the algorithm. The K-Means method is a method that aims to group several data based on the characteristics of the data quickly and efficiently. The tool used is Rapidminer software to calculate the data accounting level.